Cônicas: uma prática escolar - Puppin, Maurício (2019)
Based on the protagonism of the learner, this work aims to assist the teacher of mathematics of High School, in the teaching of Analytical Geometry, with a practical approach to facilitate the student's understanding of Conics, with emphasis on ellipse. By the use of free software Geogebra, the student can observe the translation of the curve in the plane and identify in its equation, the differences between the positions: horizontal and vertical, making learning dynamic and more effective.